IGFBP2 secretion by mammary adipocytes limits breast cancer invasion - Conway James RW; Dinc Defne D; Follain Gautier; Paavolainen Oona; Kaivola Jasmin; Boström Pia; Hartiala Pauliina; Peuhu Emilia; Ivaska Johanna (AMER ASSOC ADVANCEMENT SCIENCE, 2025)
The progression of noninvasive ductal carcinoma in situ to invasive ductal carcinoma for patients with breast cancer results in a significantly poorer prognosis and is the precursor to metastatic disease. In this work, we have identified insulin-like growth factor-binding protein 2 (IGFBP2) as a potent adipocrine factor secreted by healthy breast adipocytes that acts as a barrier against invasive progression. In line with this role, adipocytes differentiated from patient-derived stromal cells were found to secrete IGFBP2, which significantly inhibited breast cancer invasion. This occurred through binding and sequestration of cancer-derived IGF-II. Moreover, depletion of IGF-II in invading cancer cells using small interfering RNAs or an IGF-II-neutralizing antibody ablated breast cancer invasion, highlighting the importance of IGF-II autocrine signaling for breast cancer invasive progression. Given the abundance of adipocytes in the healthy breast, this work exposes the important role they play in suppressing cancer progression and may help expound upon the link between increased mammary density and poorer prognosis.